Empirical analysis of the dynamics of the South African rand (Post-1994) - May, Cyril (My University, 2016)
The objective of this thesis is to investigate the recent historical dynamics of the four major nominal bilateral spot foreign exchange rates and the fifteen currency-basket nominal effective exchange rate of the South African rand (hereafter referred to as the rand). The thesis has been organised as three separate studies that add to the advancement of the knowledge of the characteristics and behaviour (causal effects) of the rand. The common thread that holds the individual chapters together is the study of the dynamics of the rand. In particular, the study establishes whether the apparent nonstationarity of the exchange rate is a product of unit root test misspecification (a failure to account for structural change), considers the connexions between the timing of the identified structural shifts and important economic and noneconomic events, and analyses rand volatility and the temporal effect of monetary policy surprises on both the spot foreign exchange market returns and volatility of the rand. In order to do this, low- and high-frequency data are employed. With regard to exchange rate modelling, the theoretical economic-exchange rate frameworks are approached both from the traditional macro-based view of exchange rate determination and a micro-based perspective. The various methodologies applied here tackle different aspects of the exchange rate dynamics. To preview the results, we find that adjusting for structural shifts in the unit root tests does not render any of the exchange rates stationary. However, the results show a remarkable fall in the estimates of volatility persistence when structural breaks are integrated into the autoregressive conditional heteroskedasticity (ARCH) framework. The empirical results also shed light on the impact of modelling exchange rates as long memory processes, the extent of asymmetric responses to ‘good news’ and ‘bad news’, the consistencies and contrasts in the five exchange rate series’ volatility dynamics, and the timing and likely triggers of volatility regime switching. Additionally, there are convincing links between the timing of structural changes and important economic (and noneconomic) events, and commonality in the structural breaks detected in the levels and volatility of the rand. We also find statistically and economically significant high-frequency exchange rate returns and volatility responses to domestic interest rate surprises. Furthermore, the rapid response of the rand to monetary policy surprises suggests a relatively high degree of market efficiency (from a mechanical perspective) in processing this information. Keywords: Exchange rate, expectations, long memory, monetary policy surprises, repo rate, structural breaks, volatility; unit root. JEL Code: C22, E52, E58, F31, F41, G14 and G15
Thesis (Ph.D. (Economics))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic & Business Sciences, 2016.
Keywords: Foreign exchange rates--South Africa; Monetary policy--South Africa